Skipsdagboken fra hvalkokeriet "Pythia" : beriberi utbruddet i 1928 - Børresen, Dag Ingemar (Sandar historielag, 2002)
Keywords: Norge; Sørishavet; dagbøker; hvalfangst; hvalkokerier

Antarctica - Sale, Richard (To the ends of the Earth : the history of Polar exploration, 2002)
This text provides an insight into the early history of the Polar regions, and tells the stories of Man's first exploration of the Arctic and Antarctic, and subsequent expeditions. The history of individual Polar expeditions has been told many times, but usually only as personal accounts of individual adventures. This misses the overall context of polar exploration - why the British depended on ponies, or plant-eating animals (on the only continent where plants don't grow), why Franklin's men perished when the local Eskimos were eking out an existence around them (and reporting Franklin's demise), and why the Scandinavians were always better than anybody else. The first map of Antarctica was produced in 1556 - the Vikings visited the Arctic 1,000 years before. In 2001, the US Base at the South Pole is manned 365 days a year. The book tells the whole story of how the two last wildernesses, at either end of the world, were discovered, conquered and tamed.
Keywords: Antarktis; Belgica ekspedisjon; Carsten Egeberg Borchgrevink; Nordmenn; Norge; Roald Amundsen; Southern Cross; Sydpolsekspedisjonen; ekspedisjonen; historie; hvalfangst; oppdagelsesreiser; pelagisk; polareksspedisjoner